ANALISIS IMPLEMENTASI PEMBIAYAAN RAHN TASJILY TERHADAP KESESUAIANNYA DENGAN FATWA DSN-MUI NOMOR 68/DSN-MUI/III/2008 (Studi Kasus Pada KSPPS BMT Mandiri Sejahtera Jawa Timur Cabang Balongpanggang) - Masriani Mahyuddin; Ana Fitriyatul b (J-MACC, 2018)
BMT Mandiri Sejahtera East Java Branch Balongpanggang is a Sharia Financial Institution that has financing products rahn tasjily. Rahn tasjily is a product based on sharia principles where customers are not subject to additional charges from the financing of the loan. It is also reinforced by Fatwa DSN-MUI Number 68 / DSN-MUI / III / 2008. The purpose of this research is to know the implementation of rahn tasjily financing to suitability with the Fatwa DSN-MUI No.68 / DSN-MUI / III / 2008. Research approach using qualitative descriptive approach. Data collection methods used were interviews, observation and documentation. While the method of data analysis using Miles and Hubbergman. The results in this study showed on BMT Mandiri Sejahtera Jawa East Branch Balongpanggang implementation of financing rahn tasjily associated with PSAK 107 about ijara not in accordance with PSAK 107 on presentation point and its practice according to Fatwa DSN-MUI No.68 / DSN-MUI / III / 2008 not in accordance at point f and point g.